2020
DOI: 10.3389/fvets.2020.614513
|View full text |Cite
|
Sign up to set email alerts
|

High-Zinc Supplementation of Weaned Piglets Affects Frequencies of Virulence and Bacteriocin Associated Genes Among Intestinal Escherichia coli Populations

Abstract: To prevent economic losses due to post-weaning diarrhea (PWD) in industrial pig production, zinc (Zn) feed additives have been widely used, especially since awareness has risen that the regular application of antibiotics promotes buildup of antimicrobial resistance in both commensal and pathogenic bacteria. In a previous study on 179 Escherichia coli collected from piglets sacrificed at the end of a Zn feeding trial, including isolates obtained from animals of a high-zinc fed group (HZG) and a corresponding co… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 92 publications
(113 reference statements)
0
6
0
Order By: Relevance
“…Various (mainly) negative, as well as positive, correlations between free ions or protein-bound zinc and numbers of different bacterial taxa or groups in the GIT were reported by [ 18 ], while seemingly similar Zn fractions between groups have been associated with different microbial profiles [ 16 ] or apparent fractional differences between groups associated with relatively similar gut microbiological parameters [ 20 ]. Excess Zn has been reported to be negatively correlated with the occurrence of enteric E. coli pathotypes, which could at least partially explain the associated reduction in diarrhea, but seemingly increases the carriage of virulence-associated genes within the intestinal E. coli populations [ 23 ], and has been proposed to slow the decline in fecal shedding of an administered Salmonella serovar [ 24 ].…”
Section: Zinc Copper and Manganese Influences On Intestinal Healthmentioning
confidence: 99%
See 1 more Smart Citation
“…Various (mainly) negative, as well as positive, correlations between free ions or protein-bound zinc and numbers of different bacterial taxa or groups in the GIT were reported by [ 18 ], while seemingly similar Zn fractions between groups have been associated with different microbial profiles [ 16 ] or apparent fractional differences between groups associated with relatively similar gut microbiological parameters [ 20 ]. Excess Zn has been reported to be negatively correlated with the occurrence of enteric E. coli pathotypes, which could at least partially explain the associated reduction in diarrhea, but seemingly increases the carriage of virulence-associated genes within the intestinal E. coli populations [ 23 ], and has been proposed to slow the decline in fecal shedding of an administered Salmonella serovar [ 24 ].…”
Section: Zinc Copper and Manganese Influences On Intestinal Healthmentioning
confidence: 99%
“…In weaned pigs, Højberg et al [ 23 ] reported that 175 mg/kg dietary Cu (from CuSO 4 ) reduced lactic acid bacteria counts in the stomach, and coliforms in the cecum and the colon, while Namkung et al [ 40 ] found the GI microbiota diversity to be reduced with 250 mg/kg additional Cu. A lower microbiota diversity is often considered undesirable, although often a feature of antimicrobial supplementation, but the reduction in the putative beneficial lactic acid bacteria was surprising.…”
Section: Zinc Copper and Manganese Influences On Intestinal Healthmentioning
confidence: 99%
“…These studies are complicated by the fact that many pathogens of concern are opportunists and do not necessarily cause infection at the time of exposure or transmission. Therefore, colonisation, virulence potential linked to AMR and heavy metal resistance and potential for gene transfer, as well as relevance to human infection should also be considered as an end point for epidemiological studies (in addition to infection) as part of overarching One Health‐based studies (Hernando‐Amado et al., 2019; Findlay et al., 2020; Johanns et al., 2020).…”
Section: Assessmentmentioning
confidence: 99%
“…A detailed analysis of 179 Escherichia coli genomes obtained from piglets after completion of a Zn oxide feeding trial demonstrated that genes and operons associated with virulence and bacteriocin production, as well as enterotoxigenic, enteropathogenic, and Shiga toxin-producing pathotypes were less abundant in high Zn-supplemented animals [ 66 ]. In enteropathogenic Escherichia coli , exposure to Zn was shown to reduce expression of virulence factors and reduced bacterial adhesion to the cells.…”
Section: Zn and Microbiota Upon Exposure To Toxic And Infectious Agentsmentioning
confidence: 99%